Activated carbon cryogel as a potential adsorbent for removal of aspirin - Mohd Asraff, Asmadi; Nor Aishah, Saidina Amin; Muzakkir Mohammad, Mohammad Zainol; Marfiah, Ab Wahid; Sureena, Abdullah; Khor, Wai Mun (AIDIC Servizi, 2021)
Pharmaceutical substances are urged to be removed from wastewater as the pollutants bring adverse effects to both humans and the environment. Among the pharmaceutical substances, aspirin is selected as the targeted pharmaceutical waste due to its extremely high consumption. Aspirin is widely used in the world and is produced about 35,000 t/y. Carbon cryogel was chosen as the potential adsorbent to remove aspirin from wastewater, and it was synthesized from urea and furfural before activation with H3PO4. The effects of experimental parameters on aspirin adsorption such as pH, contact time, initial concentration, adsorbent dosage, and temperature were investigated. A maximum of 30 % of percentage removal and 30 mg/g of adsorption capacity were achieved at an initial concentration of 60 mg/L, pH 6, and 0.05 g of adsorbent at room temperature after 45 min of contact time. The activated carbon cryogel synthesized in this study is useful for application in wastewater treatment and sanitation of water